Healing of ExcisionAl wounds on Lower legs by Secondary intention (HEALS) cohort study. Part 2: feasibility data from a multicentre prospective observational cohort study to inform a future randomized controlled trial. (27th July 2022) - Gilberts, Rachael; McGinnis, Elizabeth; Ransom, Myka; Pynn, Emma V.; Walker, Benjamin; Brown, Sarah; Trehan, Pooja; Jayasekera, Prativa; Veitch, David; Hussain, Walayat; Collins, Jemma; Abbott, Rachel Angharad; et al.
Abstract: Background: Compression therapy is considered beneficial for postsurgical lower leg wound healing by secondary intention; however, there is a lack of supportive evidence. To plan a randomized controlled trial (RCT), suitable data are needed. Aim: To determine the feasibility of recruitment and estimate recruitment rate; to understand the standard postoperative wound management pathway; to determine uptake of optional additional clinic visits for healing confirmation; and to explore patient acceptability of compression bandaging and plan a future RCT. Methods: Participant recruitment was performed from secondary care dermatology clinics, during a period of 22 months. Inclusion criteria were age ≥ 18 years, planned excision of keratinocyte cancer on the lower leg with healing by secondary intention and an ankle–brachial pressure index of ≥ 0.8. Exclusion criteria were planned primary closure/graft or flap; inability to receive, comply with or tolerate high compression; planned compression; or suspected melanoma. Patients were followed up weekly (maximum 6 months) in secondary care clinics and/or by telephone. Information was collected on healthcare resource use, unplanned compression, wound healing and an optional clinic visit to confirm healing. Results: This study recruited 58 patients from 9 secondary care dermatology clinics over 22 months. Mean recruitment/centre/month was 0.8 (range 0.1–2.3). Four centres had dedicated Research Nurse support. The analysis population ( n = 53) had weekly follow‐up assessments. Standard care clinical contacts were: general practitioner (7 visits; 1.2%), community nurse (169; 28.5%), practice nurse visits (189; 31.8%) and dermatology clinic visits (138; 23.2%). Participants whose wounds healed (34 of 45; 75.6%) attended an optional clinic visit. Conclusion: Data were obtained to inform a future RCT. Recruitment rates were found to be higher in centres with dedicated research support. People would be willing to take part in a trial and attend a confirmation of healing visit. Abstract : Compression therapy may be beneficial for healing of surgical wounds following excision of keratinocyte cancer of the lower leg. The paper presents additional feasibility findings of a cohort study performed to inform a randomized controlled trial design. It includes estimates of recruitment rates, postoperative wound management pathways and a report of a Patient and Public Involvement meeting to explore acceptability of types of compression and willingness to participate in a trial.